Step-by-step explanation:
The first set is equivalent.
We obtain the right-hand side by swapping places of the terms.
Answer:
-2x² - 16x + 4
Step-by-step explanation:
Step 1: Write out expression
6x² - 9x + 3 - (8x² + 7x - 1)
Step 2: Distribute negative
6x² - 9x + 3 - 8x² - 7x + 1
Step 3: Combine like terms (x²)
-2x² - 9x + 3 - 7x + 1
Step 4: Combine like terms (x)
-2x² - 16x + 3 + 1
Step 5: Combine like terms (constants)
-2x² - 16x + 4
For number 1 and 2 you are correct but I'm not sure for number 3
Answer:
Angl.(QMT) = 134°
Angl.(QMT) = Angl.(QMS)+ Angl.(SMT)
or, 134°= (7x-4)° + (2x+3)°
or, 134° = 7x + 2x -4° +3°
or, 134° = 9x -1°
or, 134° + 1° = 9x
or, 135° = 9x
or, 135°/9° = x
or, 45° = x
x=45°
Answer:
work is shown and pictured